Perineal myxoid liposarcomas: a case report and literature review - Ramasamy, Prabhu; Md Nor, Azmi; Mohamed Kamil, Nil Amri; Harun, Norra; Mohd Yusof, Mubarak; Mat Hassan, Mohd. Zailani (Universiti Sains Malaysia, 2010)
Myxoid liposarcoma is the major subtype of liposarcoma and commonly presents in the extremities, particularly in the thigh. We introduce an unusual case of a myxoid liposarcoma presenting as a large perineal swelling occupying the para-rectal and para-anal spaces in a 49-year-old male patient. The diagnosis, management, and prognosis of myxoid liposarcoma are discussed. A literature review is performed for myxoid liposarcoma.